2019
DOI: 10.1021/acs.jafc.9b01106
|View full text |Cite
|
Sign up to set email alerts
|

Pectin/Chitosan/Tripolyphosphate Nanoparticles: Efficient Carriers for Reducing Soil Sorption, Cytotoxicity, and Mutagenicity of Paraquat and Enhancing Its Herbicide Activity

Abstract: As a potent herbicide capable of contaminating water and soil environments, paraquat, which is still widely used worldwide, is toxic to mammals, algae, aquatic animals, etc. Paraquat was loaded on novel nanoparticles composed of pectin, chitosan, and sodium tripolyphosphate (PEC/CS/TPP). The size, polydispersity index, and ζ potential of nanoparticles were characterized. Further assessments were carried out by SEM, AFM, FT-IR, and DSC. The encapsulation was highly efficient, and there was a delayed release pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Chitin and chitosan formulations can also be used as a carrier to maximize herbicide activity thus reducing their dangerous accumulation in the environment. For example, paraquat loaded into chitosan nanoparticles shows enhanced herbicide activity accompanied by decreased soil penetration, cytotoxicity and mutagenicity [62] and chitosan/glyphosate formulations show less phytotoxicity and better herbicidal activity than the commonly used salt form of glyphosate [63]. Finally, chitosan supplementation can help to reduce the environmental impact in terms of greenhouse gas emissions and soil acidification of industrial wastewater treatments with respect to the existing chemical treatment process [64].…”
Section: Chitin-and Chitosan-based Derivatives In Recovery Of Contamimentioning
confidence: 99%
“…Chitin and chitosan formulations can also be used as a carrier to maximize herbicide activity thus reducing their dangerous accumulation in the environment. For example, paraquat loaded into chitosan nanoparticles shows enhanced herbicide activity accompanied by decreased soil penetration, cytotoxicity and mutagenicity [62] and chitosan/glyphosate formulations show less phytotoxicity and better herbicidal activity than the commonly used salt form of glyphosate [63]. Finally, chitosan supplementation can help to reduce the environmental impact in terms of greenhouse gas emissions and soil acidification of industrial wastewater treatments with respect to the existing chemical treatment process [64].…”
Section: Chitin-and Chitosan-based Derivatives In Recovery Of Contamimentioning
confidence: 99%
“…This value can be due to the particles forming aggregates during sample preparation for analysis, which was subjected to a vacuum drying process. Previous studies have demonstrated that non-covalent interactions, such as hydrogen bonding and electrostatic interactions, favour the formation of aggregates or a packed matrix [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, chitosan–pectin complexes have shown resistance to UV action higher than homopolymers, which is a desirable property in medical or pharmaceutical applications [ 15 ]. A few research papers have been focused on the encapsulation process using the pectin polymer, as for example the polyelectrolytes of pectin–chitosan to encapsulate insulin [ 16 ], zein–pectin nanoparticles to carry up curcumin [ 17 ], and pectin–chitosan-tripolyphosphate nanoparticles to encapsulate the herbicide Paraquat [ 18 ]. Our study complements previous works by an evaluation of DE of the pectin in the polyelectrolyte formation, the temperature effect on the stability of the polyelectrolytes based on amphiphilic chitosan (AmCh) and pectin, and the capacity of the polyelectrolytes to encapsulate the Nile Red (NR), a solvatochromic fluorophore with different behavior in polar and no polar environment.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were cultured in RPMI 1640 medium supplemented with 10% FBS, 2mM Gln, penicillin (100 U/mL), and streptomycin (100 μg/mL) in humidified 5% CO2, the atmosphere at 37°C temperature. For ChiNH, Q, and ChiNH/Q treatment, cells were seeded into six-well plates at a density of 3 × 10 4 cells and allowed to attach for 24 h. The viability of HepG2 cells was determined by MTT test using 5 different concentrations of 10, 50, 100, 500 and 1000 µg/mL of ChiNH, Q and ChiNH/Q for 48h based on the method described by Rashidipour et al 52 All experiments were performed in triplicate and the data were expressed as mean ± SD. Antimicrobial effects of broth microdilution were used according to the CLSI standard method.…”
Section: Hepg2 Cell Culture and Mtt Assaymentioning
confidence: 99%